Penggunaan Media Sosial Instagram Sebagai Pendorong Keinginan Berolahraga Pada Komunitas Pelarian IPB - Novi Kristiawati; Hudi Santoso; Enden Darjatul Ulya; Fahmi Fuad Cholagi; Hadiyanto (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2026)
The development of digital technology has increased the use of social media as a means of communication and motivation, including in sports activities. Instagram, as a visual platform, is widely used to build identity and encourage interaction between users. This study aims to analyze the use of Instagram and the level of desire to exercise, as well as to test the relationship between the two in the IPB Running Community, a student running community that actively uses Instagram for documentation and member motivation. The study used a quantitative approach with a correlational descriptive method. Data were obtained through an online questionnaire administered to 89 respondents selected using the Slovin formula. The results showed that Instagram usage was in the good category in terms of information, identity, personal motivation, social integration, and entertainment. The members' desire to exercise was also in the high category. Spearman's correlation test showed a significant relationship between Instagram usage and the desire to exercise in this community. This study contributes theoretically to the study of digital communication and has practical implications for sports communities in optimizing social media to increase member motivation and participation in a healthy lifestyle.